Penerapan Permainan Alphabet Fishing Interactive Untuk Meningkatkan Kemampuan Mengenal Huruf Di TKM NU 14 Al Mustaqim Sitirejo Wagir - Risa Kurniawati; Mochammad Ramli Akbar; Ayu Asmah (Universitas Nusantara PGRI Kediri, 2026)
This study was motivated by the low level of basic literacy skills, particularly letter recognition, among Group A children at TKM NU 14 Al Mustaqim Sitirejo Wagir. A total of 73% of the children were still categorized as Not Yet Developed (BB) and Beginning to Develop (MB) in distinguishing letter shapes and associating sounds with alphabet symbols. This study aimed to improve these skills through the use of the Alphabet Fishing Interactive game media. The method employed was a collaborative Classroom Action Research (CAR) conducted in two cycles involving 10 children as participants. Data were collected through observation and documentation and analyzed based on children's developmental categories (BB, MB, BSH, BSB). The results showed a consistent improvement in letter recognition skills, increasing from 37.5% in the pre-cycle to 66.25% at the end of Cycle I and reaching 85% in Cycle II with the category Very Well Developed (BSB). These findings indicate that the Alphabet Fishing Interactive game is effective in improving children's letter recognition skills by providing concrete, multisensory, and play-based learning experiences